Scientific and Educational Potential of The Educational Base "Gornoye" of The State University of Land Use Planning as a System of Monitoring Indicators for The Environmentally Sustainable Development of The Region - Yuliya, Yurova; Vera, Shirokova; Alla, Khutorova (Journal of Sustainability Perspectives, 2021)
The use of green campus practices by the State University of land use planning promotes a culture of sustainable development for all stakeholders. One of the forms of interaction was the scientific and educational base (SEB) Gornoye. The territory of the SEB "Gornoye" combines unique physical, geographical and agricultural features necessary for performing the educational, scientific, applied, research and production functions of the Department and is designed to ensure the sustainable development of natural territories.